2021
DOI: 10.1016/j.isci.2021.102427
|View full text |Cite|
|
Sign up to set email alerts
|

Myeloid Nrf2 deficiency aggravates non-alcoholic steatohepatitis progression by regulating YAP-mediated NLRP3 inflammasome signaling

Abstract: Highlights Kupffer cells Nrf2 was downregulated in both human and mouse NASH livers Myeloid Nrf2 deficiency aggravates liver steatosis and inflammation in HFDinduced NASH Nrf2 controls the NLRP3 activation in a ROSmediated Hippo-YAP signaling manner

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 46 publications
3
14
0
1
Order By: Relevance
“…In line with our results, the activation of NRF2 protected against hepatocyte steatosis in nutritionally induced nonalcoholic steatohepatitis in mice . Furthermore, myeloid NRF2 deficiency aggravated nonalcoholic steatohepatitis progression . However, some study also reported that hepatocyte-specific NRF2 deficiency mitigated high-fat-diet-induced hepatic steatosis .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In line with our results, the activation of NRF2 protected against hepatocyte steatosis in nutritionally induced nonalcoholic steatohepatitis in mice . Furthermore, myeloid NRF2 deficiency aggravated nonalcoholic steatohepatitis progression . However, some study also reported that hepatocyte-specific NRF2 deficiency mitigated high-fat-diet-induced hepatic steatosis .…”
Section: Discussionsupporting
confidence: 90%
“…63 Furthermore, myeloid NRF2 deficiency aggravated nonalcoholic steatohepatitis progression. 64 However, some study also reported that hepatocyte-specific NRF2 deficiency mitigated high-fat-diet-induced hepatic steatosis. 65 NRF2 also promoted the development of fibrosis and tumorigenesis in mice with defective hepatic autophagy.…”
Section: ■ Discussionmentioning
confidence: 99%
“…In NASH models, the NLRP3 inflammasome activation in KCs or BMDMs caused inflammatory cytokine production, contributing to lipid synthesis in hepatocytes and fibrotic collagen production in HSCs ( 71 73 ). Furthermore, macrophage-specific Nrf2 knockout aggravated NASH progression by initiating ROS and IL-1β in a yes-associated protein (YAP)–NLRP3-dependent manner ( 74 ). This finding demonstrates the role of ROS in activating the NLRP3 inflammasome in NASH.…”
Section: Inflammasome and Pyroptosis In Liver Fibrosismentioning
confidence: 99%
“…Similarly, Nrf2 can increase NQO1 production and lead to negative effects on NLRP3 inflammasome activation (200). In addition, Hippo-yes-associated protein signaling can also be viewed as a mechanism of Nrf2 activation alleviating inflammation related to NLRP3 inflammasome activation (202).…”
Section: Nrf2 and Nf-kb Signalingmentioning
confidence: 99%